Physical activity levels are positively related to progression-free survival and reduced adverse events in advanced ER+ breast cancer - Zimmer, Philipp; Esser, Tobias; Lueftner, Diana; Schütz, Florian; Baumann, Freerk T.; Rody, Achim; Schneeweiss, Andreas; Hartkopf, Andreas D.; Decker, Thomas; Uleer, Christoph; Stoetzer, Oliver J.; Foerster, Frank; et al. (BMC medicine, 2024)
Increased levels of physical activity are associated with a reduction of breast cancer mortality, especially in postmenopausal women with positive hormone receptor status. So far, previous observational case-control and cohort studies have focused on associations between overall leisure time physical activity and survival of women with breast cancer in general. In this multicenter prospective cohort study, conducted in Germany between 30th August 2012 to 29th December 2017, we investigated general physical activity in a homogenous sample of n = 1440 postmenopausal women with advanced (inoperable locally advanced or metastatic), hormone receptor-positive breast cancer receiving the same therapy (everolimus and exemestane). Self-reported physical activity was assessed using the Godin Leisure Time Exercise Questionnaire (GLTEQ) before and every 3 months during treatment. Participants were then classified into “active” and “insufficiently active” to screen their activity behavior the week prior to medical treatment. In addition, changes in physical activity patterns were assessed. Adjusted Cox regression analyses were performed for the activity categories to determine hazard ratios (HR). Besides progression-free survival (PFS), adverse events (AEs), QoL, and fatigue were assessed every 3 months until study termination. Compared to “insufficiently active” patients, “active” individuals indicated a significantly longer PFS (HR: 0.84 [0.74; 0.984], p = .0295). No significant differences were observed for changes of physical activity behavior. Patients who reported to be “active” at baseline revealed significantly fewer AEs compared to “insufficiently” active patients. In detail, both severe and non-severe AEs occurred less frequently in the “active” patients group. In line with that, QoL and fatigue were better in physical “active” patients compared to their insufficient active counterparts at the last post-baseline assessment. Participants who remained or become active indicated less AEs, a higher QoL, and reduced fatigue levels. Physical activity behavior prior to medical treatment might have prognostic value in patients with advanced breast cancer in terms of extending the PFS. Moreover, physical activity before and during treatment may reduce treatment-related side effects and improve patients’ QoL and fatigue. EUPAS9462. Registered 30th October 2012 “retrospectively registered.”
Im Titel erscheint das + hochgestellt
Gesehen am 28.04.2025